(untitled) (International Journal of Scientific Trends, 2024)
This article presents the role of hypocoristics, that is, diminutive forms of the name in an onomastic unit, as well as an analysis of studies of the role of hypocoristics in onomastic units. It is said that the study of the features of its development and application is of great scientific importance. Also, examples demonstrate the study of hypocharistics in the Uzbek and English languages and the features of these motives. The theoretical information and views of researchers conducting scientific research in the areas of Uzbek and English anthroponymy are studied.